2018
DOI: 10.1080/03054985.2018.1438255
|View full text |Cite
|
Sign up to set email alerts
|

The mainstreaming of charities into schools

Abstract: This paper focuses on the 'mainstreaming' of charities into schools. There have been growing concerns about the permeation of business and business values in education, but relatively little attention has been paid to the ways in which schools are increasingly engaged in the 'business' of fundraising for charities. Drawing on survey data from the WISERDEducation Multi-Cohort Study (WMCS), the paper outlines young people's relationship with charities. The data show that young people have a high degree of engage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 19 publications
2
26
0
Order By: Relevance
“…In keeping with previous research, we find that children demonstrate high levels of altruism and understanding about charity and charitable giving, recognising it as a space in which to achieve social good (Power and Taylor, ). However, this ethnographic style study about children’s experiences revealed two key features, which ultimately present as two sides of the same coin.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…In keeping with previous research, we find that children demonstrate high levels of altruism and understanding about charity and charitable giving, recognising it as a space in which to achieve social good (Power and Taylor, ). However, this ethnographic style study about children’s experiences revealed two key features, which ultimately present as two sides of the same coin.…”
Section: Resultssupporting
confidence: 90%
“…As Peterson (2019) points out, engagement in communities and deliberation with others is central to developing individual character, alongside recognising and challenging structural injustices. Power and Taylor (2018) identify charities are increasingly becoming mainstream in schools and most of the big charitable campaigns have established resource packs to assist schools in fundraising or social action endeavours. However, we raise concern with this, while such activity may increase children's experiences of charitable fundraising and volunteering, it is at risk of marginalising their critical enquiry into the cause areas, as well as offers a very limited view of the charitable sector.…”
Section: Spaces In Which Children Engage In Charitable Givingmentioning
confidence: 99%
See 3 more Smart Citations